(untitled) (Research, Society and Development, 2023)
The objective of this project was to determine the antimicrobial activity of extracts from the stem of Solanum lycocarpum St. Hill. The extraction was carried out by the drag method with polarities ranging from non-polar to more polar solvents. After performing a qualitative phytochemistry, the antimirobial tests performed were the minimun and maximum inhibitory concentration, kinetic curve of bacterial growth, disk-diffusion test and minimum bactericidal concentration. Each test is related and together They can determine the antimicrobial potential, if the phytoconstituents of each extract and polarity are bactericidal or bacteriostatic and related to bacterial resistence events. The trials showed that the minimum dose of extract for all strains was above 20 mg and the maximum between 160 – 180 mg. The assays also showed resistance events for Gram negatives strains (E. coli and P. aeruginosa). Therefore, Lobeira bioactives have antimicrobial activity, being bactericidal and bacteriostatic.